CHEMICALLY CHITOSAN MODIFIED WITH METHYL METHACRYLATE AND ITS EFFECT ON MECHANICAL AND THERMAL PROPERTIES OF POLYPROPYLENE COMPOSITES - Faisal Amri Tanjung; Salmah Husseinsyah; Kamarudin Hussin; Iqmal Tahir (Universitas Gadjah Mada, 2013)
Effects of methyl methacrylate on the properties of chitosan-filled polypropylene (PP) composites has been investigated. Mechanical and thermal properties of the composites were analyzed according to ASTM D 638-91, thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC). The results showed that tensile strength of PP composites decreased upon the addition of chitosan, while Young's modulus improved. At a similar filler loading, the treated PP/chitosan composites were found to have higher tensile strength and Young's modulus as compared with the untreated composites. Thermal analysis results showed that thermal stability and crystallinity of the treated composites were higher than the untreated ones. Scanning electron microscopy (SEM) and Fourier transforms infrared (FTIR) studies revealed less detached filler from matrix on tensile surface of the treated composites as an evidence of enhanced filler-matrix interfacial adhesion due to formation of ester-bridge between the chitosan and the methyl methacrylate.